Hyperfunctioning Papillary Thyroid Carcinoma with a BRAF Mutation: The First Case Report and a Literature Review. Issue 3 (5th June 2021) - Shinkai, Shinsuke; Ohba, Kenji; Kakudo, Kennichi; Iwaki, Takayuki; Mimura, Yoshihiro; Matsushita, Akio; Kuroda, Go; Sakai, Yuki; Nishino, Nobuhiko; Umemura, Kazuo; Suda, Takafumi; Sasaki, Shigekazu
Abstract : Introduction: Hyperfunctioning papillary thyroid carcinoma (PTC) is rare and consequently, little information on its molecular etiology is available. Although BRAF V600E ( BRAF c.1799T>A, p.V600E) is a prominent oncogene in PTC, its mutation has not yet been reported in hyperfunctioning PTC. Case Presentation: Ultrasonography detected a 26-mm nodule in the right lobe of the thyroid gland of a 48-year-old man. Thyroid function tests indicated that he was hyperthyroid with a TSH level of 0.01 mIU/L (reference range: 0.05–5.00) and a free thyroxine level of 23.2 pmol/L (reference range: 11.6–21.9). TSHR autoantibodies were <0.8 IU/L (reference value: <2.0 IU/L). The 99m Tc thyroid scintigram revealed a round, right-sided focus of tracer uptake by the nodule with a decreased uptake in the remainder of the gland. The patient underwent total thyroidectomy because fine-needle aspiration cytology revealed a malignancy. The histopathological diagnosis was conventional PTC. Subsequent mutational analysis of BRAF (exon 15), TSHR (exons 1–10), GNAS (exons 7–10), EZH1 (exon 16), KRAS, NRAS, HRAS (codons 12, 13, and 61), and TERT promoter (C250T and C228T) identified a heterozygous point mutation in BRAF V600E in a tumor tissue sample. In addition, we identified a TSHR D727E polymorphism ( TSHR c.2181C>G, p.D727E) in both the tumor and the surrounding normal thyroid tissue. Discussion and Conclusions: We report a case of hyperfunctioning PTC with a BRAF V600E mutation for the first time. Our literature search yielded 16 cases of hyperfunctioning thyroid carcinoma in which a mutational analysis was conducted. We identified TSHR mutations in 13 of these cases. One case revealed a combination of TSHR and KRAS mutations; the other case revealed a TSHR mutation with a PAX8/PPARG rearrangement. These findings suggest that the concomitant activation of oncogenes (in addition to constitutive activation of the TSHR-cyclic AMP cascade) are associated with the malignant phenotype in hyperfunctioning thyroid nodules.